Pengelolaan Lahan Rawa Gambut Terdegradasi Melalui Pengayaan Karbon Mendukung Ketahanan Pangan Beras - Najib Asmani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Najib, A. 2012.Â Managing Degraded Peatland through Carbon Enhacement to Support Rice Security. J. Lahan Suboptimal 1(1):83-91.Indonesia often faces food problem, especially rice as the staple food for most Indonesian. To support rice security, the Government of Indonesia has made serious efforts to increase rice productivity through cultivating suboptimal land. However, utilizing it in unwise ways, especially for the degraded peatland, could release green house gases. Utilization of peatland for rice field should be done simultaneously with wise conservation to enhance carbon stock. It should be managed in a good way in order to avoid the increaseof carbon dioxide emission. The addition of carbon from this activity could be considered as a potential carbon incentive if REDD+ scheme be ratified officially. As a result, farmer would be able to receive carbon incentive as their additional income.